A COMPREHENSIVE REVIEW ON-APPLICATION AND FUTURE PROSPECT OF CYTOPLASMIC MALE STERILITY - Sujan Chapagain (Acta Scientifica Malaysia)
Cytoplasmic male sterility (CMS) is a plant’s inability to reproduce fertile pollen due to nuclear and mitochondrial genomic incompatibility. In CMS plants, pollen production is disrupted, but this can be restored by nuclear fertility (Rf) genes, while the function of the female organ is typically unaffected. CMS has been intensively used for F1 seed production in self-pollinating crops and practical applications in plant breeding. This comprehensive review explores the intricate mechanisms, applications, limitations, advancements, and prospects of CMS in an agricultural context. Despite its notable advantages, CMS does present limitations, such as instability and genetic vulnerabilities, which are discussed alongside strategies for mitigation. Moreover, the review elucidates on the recent advancements in biotechnology, omics technologies, and breeding approaches, which promise to further harness the potential of CMS in addressing global food security challenges. From the identification of diverse CMS sources to the utilization of advanced genetic engineering techniques like CRISPR-Cas gene editing, the future of CMS in crop breeding appears promising. Thus, the development of diverse sources of CMS and its practical application in breeding are expected in the future.